Single Cell Transcriptome Sequencing of Zebrafish Testis Revealed Novel Spermatogenesis Marker Genes and Stronger Leydig-Germ Cell Paracrine Interactions - Qian, Peipei; Kang, Jiahui; Liu, Dong; Xie, Gangcai (Frontiers in Genetics, 2022)
Spermatogenesis in testis is an important process for sexual reproduction, and worldwide about 10-15 percent of couples suffer from infertility. It is of importance to study spermatogenesis at single cell level in both of human and model organisms. Currently, single-cell RNA sequencing technologies (scRNA-seq) had been extensively applied to the study of cellular components and its gene regulations in the testes of different species, including human, monkey, mouse, and fly, but not in zebrafish. Zebrafish was a widely used model organism in biology and had been extensively used for the study of spermatogenesis in the previous studies. Therefore, it is also important to profile the transcriptome of zebrafish testis at single cell level. In this study, the transcriptomes of 14, 315 single cells from adult male zebrafish testes were profiled by scRNA-seq, and 10 cell populations were revealed, including Leydig cell, Sertoli cell, spermatogonia cell (SPG), spermatocyte, and spermatids. Notably, thousands of cell-type specific novel marker genes were identified, including sumo3b for SPG, krt18a.1 for Sertoli cells, larp1b and edrf1 for spermatids, which were also validated by RNA in situ hybridization experiments. Interestingly, through Ligand-Receptor (LR) analyses, zebrafish Leydig cells demonstrated stronger paracrine influence on germ cells than Sertoli cells. Overall, this study could be an important resource for the study of spermatogenesis in zebrafish and might also facilitate the study of the genes associated with human infertility through using zebrafish as a model organism.